Potential Gain in Customer Value and Customer Satisfaction Index Method For Analysis of Customer Satisfaction Level (Case Study In Pt. Anteraja) - Sancha Arema Data; Ribangun Bamban Jakaria (Procedia of Engineering and Life Science, 2021)
UD PT. Tri Adi Bersama is a technology-based shipping service company known as Anteraja and sends packages by courier called Satria. This company is a supporter of Tokopedia's ecommers and will expand to other marketplaces. Currently, staging stores exist throughout Indonesia, except Papua. In the world of expedition or competing services from various companies, there are so many companies, but from all of that companies must think creatively in the services they provide to customers or consumers, companies must compete - competing for creativity in program problems that they will apply in their promotional system. Other online services have also been rampant in the general public and for competitors they also have promo programs and express facilities have tough challenges compared to other services which are only in the form of dropship services in staging areas. The Pick Up service is a service that is featured from the expedition of the Triputra group with a specified pick-up period, so the shiper or what can be called the shop owner can control and manage delivery schedules without being confused about delays in delivery The purpose of this research is to obtain complaint data to evaluate the level of customer satisfaction so that it can be used as a benchmark for companies in improving their service systems to customers using the CSI and PGCV methods.